Supramolecular Biopolymers for Tissue Engineering - Rosario Pérez-Pedroza; Alan Ávila-Ramírez; Zainab Khan; Manola Moretti; Charlotte A. E. Hauser (Advances in Polymer Technology)
Supramolecular biopolymers (SBPs) are those polymeric units derived from macromolecules that can assemble with each other by noncovalent interactions. Macromolecular structures are commonly found in living systems such as proteins, DNA/RNA, and polysaccharides. Bioorganic chemistry allows the generation of sequence-specific supramolecular units like SBPs that can be tailored for novel applications in tissue engineering (TE). SBPs hold advantages over other conventional polymers previously used for TE; these materials can be easily functionalized; they are self-healing, biodegradable, stimuli-responsive, and nonimmunogenic. These characteristics are vital for the further development of current trends in TE, such as the use of pluripotent cells for organoid generation, cell-free scaffolds for tissue regeneration, patient-derived organ models, and controlled delivery systems of small molecules. In this review, we will analyse the 3 subtypes of SBPs: peptide-, nucleic acid-, and oligosaccharide-derived. Then, we will discuss the role that SBPs will be playing in TE as dynamic scaffolds, therapeutic scaffolds, and bioinks. Finally, we will describe possible outlooks of SBPs for TE.